2017
DOI: 10.1038/npp.2017.257
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Reduces Alcohol Cue-Reactivity in Alcohol-Dependent Rats and Humans

Abstract: Approved pharmacological treatments for alcohol use disorder are limited in their effectiveness, and new drugs that can easily be translated into the clinic are warranted. One of those candidates is oxytocin because of its interaction with several alcohol-induced effects. Alcohol-dependent rats as well as post-mortem brains of human alcoholics and controls were analyzed for the expression of the oxytocin system by qRT-PCR, in situ hybridization, receptor autoradiography ([I]OVTA binding), and immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 86 publications
8
76
1
2
Order By: Relevance
“…After acute withdrawal, oxytocin system was profoundly altered as Oxt transcript level was reduced in the hypothalamus of nPE1 +/+ mice (Figure A) (Table B). Our finding is consistent with many studies showing that there are alcohol‐withdrawal related decreases in Oxt or Avp cytoplasmic mRNA and peptide levels in the hypothalamus (including the paraventricular nucleus) of mice, rats and humans . In several selectively bred alcohol drinking rat lines, there are lower basal levels of Avp mRNA in the hypothalamus of Indiana and Sardinian alcohol non‐preferring rats, as compared with their alcohol preferring counterparts .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After acute withdrawal, oxytocin system was profoundly altered as Oxt transcript level was reduced in the hypothalamus of nPE1 +/+ mice (Figure A) (Table B). Our finding is consistent with many studies showing that there are alcohol‐withdrawal related decreases in Oxt or Avp cytoplasmic mRNA and peptide levels in the hypothalamus (including the paraventricular nucleus) of mice, rats and humans . In several selectively bred alcohol drinking rat lines, there are lower basal levels of Avp mRNA in the hypothalamus of Indiana and Sardinian alcohol non‐preferring rats, as compared with their alcohol preferring counterparts .…”
Section: Discussionsupporting
confidence: 93%
“…Avp cytoplasmic mRNA and peptide levels in the hypothalamus (including the paraventricular nucleus) of mice, rats and humans. 14,[46][47][48][49] In several selectively bred alcohol drinking rat lines, there are lower basal levels of Avp mRNA in the hypothalamus of Indiana and Sardinian alcohol non-preferring rats, as compared with their alcohol preferring counterparts. 48,50 Consistent to this notion, the present study showed a lower basal Avp transcript level in nPE1 −/− mice, which could contribute to their lowered alcohol consumption and/or preference.…”
Section: Genetically Determined Differences In Stress Genes Transcrmentioning
confidence: 99%
“…Following repeated cycles of chronic intermittent alcohol vapor exposure to induce dependence in rats, Hansson and colleagues injected (icv) oxytocin in alcohol-dependent and non-dependent rats trained to orally self-administer alcohol using operant conditioning procedures. Central administration of oxytocin reduced cue-induced alcohol relapse-like behavior in alcohol-dependent rats, but not in non-dependent rats (Hansson et al, 2017). Additionally, the authors demonstrated that oxytocin mRNA was reduced in the NAc by acute alcohol and during early withdrawal, but increased after prolonged (3weeks) abstinence, suggesting dynamic dependence-related neuroadaptations of the oxytocin system.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 99%
“…Exogenous oxytocin administered to animal models has been found to reduce consumption, withdrawal symptomology, and relapse associated with many drugs of abuse, including stimulants, opioids, and alcohol (Lee and Davis 1997;Kovács et al 1998;Carson et al 2010;Bowen et al 2011;Bahi 2015;Baracz et al 2016;Bowen and Neumann 2017;Cox et al 2017;Kohtz et al 2018). In particular, oxytocin may be an effective treatment for alcohol addiction as intranasal oxytocin administration has been found to reduce alcohol craving, consumption, and withdrawal symptoms in alcohol-dependent patients, as well as reduce neural activity in response to alcohol-related cues in heavy drinkers (Pedersen et al 2013;Mitchell et al 2016;Hansson et al 2018). However, the precise mechanism by which oxytocin decreases alcohol intake and withdrawal symptoms is not yet known.…”
Section: Oxytocin and Alcohol Drinkingmentioning
confidence: 99%